Application of Motion and Song Media in Mastery of "不", "没" and "Tidak" Which is Bahasa Indonesia Equivalents (Perspective of Applied Contrastive Analysis) - Kurnia, Intan; Lutvianda, Geabby Eka; Cheryl, Euodia Elizabeth; Adhimas, Yogi Bagus (Journal of Maobi, 2023)
Contrastive analysis aimed at comparing two languages that are not cognate but are sought for similarities. Contrastive analysis has two types: pure contrastive analysis and applied contrastive. Pure contrastive analysis is linguistic analysis that compares first and second languages in linguistic typology studies, while applied contrastive analysis is linguistic analysis that compares first and second languages to solve pedagogical problems of language learning. The results of this study come from boria songs that have been modified with the discussion of 不 (bù) and 没 (méi) in the song lyrics already contained the correct use of the words 不 (bù) and 没 (méi). In this study of motion media and songs 不 (bù) and 没 (méi), researchers make interpretations by pouring all movements and songs into stanzas and then the verse will be analyzed.